Project Management - Watt, Adrienne; Open Textbook Library (Open Textbook Library, 2014)
This book covers the basics of project management. This includes the process of initiation, planning, execution, control and close out that all projects share.
1. Project Management: Past and Present -- 2. Project Management Overview -- 3. The Project Life Cycle (Phases) -- 4. Framework for Project Management -- 5. Stakeholder Management -- 6. Culture and Project Management -- 7. Project Initiation -- 8. Overview of Project Planning -- 9. Scope Planning -- 10. Project Schedule Planning -- 11. Resource Planning -- 12. Budget Planning -- 13. Procurement Management -- 14. Quality Planning -- 15. Communication Planning -- 16. Risk Management Planning -- 17. Project Implementation Overview -- 18. Project Completion -- 19. Celebrate! -- Appendix 1: Project Management PowerPoints -- Appendix 2: Chapter Questions -- Appendix 3: Chapter Audio Files -- About the Author -- Versioning History
In English.
Description based on print resource
Keywords: Business -- Textbooks; Management -- Textbooks